(untitled) (Altre Modernità, 2011)
The Jewish theatre in Hebrew has its very first beginning in Italy with the "Wedding Comedy" by Leone de Sommi (Mantua, floruit 1550), whose inspiration owes much to the Purim tradition. Jewish theatre, especially the Judaeo-Italian one, continues to flourish until XX century, always maintaining a strong connection with the Purim celebration. This article will deal with the development of the Jewish theatre - both in Hebrew and in Jewish language -, with particular emphasis on its relationship with the Purim. In examining the main phases of such a relevant phenomenon we will rely on the documents currently known, with particular reference to the Judaeo Italian corpus; one of the first objectives of this work will be to open new perspectives for further research in the field of Jewish dramatic literature.